Sustainability Evaluation of the 'Batu Into Green' Village Based on the United Nation Sustainable Development Goals (SDGs) - Sari, Hela Radika; Yusran, Yusfan Adeputera; Wulandari, Lisa Dwi; Santoso, Joko Triwinarto; Nordin, Jestin (Fakultas Teknik Universitas Brawijaya, 2024)
Nowadays, environmental issues deserve everyone's attention. People can actually improve their surrounding environment to be healthier and more comfortable, started with their own houses. This idea realizes an ecology village named 'Batu Into Green', located in Pattimura V, Temas, in the City of Batu, Indonesia. Originally, this village was a slum, but with the initiation of the local village head and with the increase of local public awareness for a healthier environment, the locals improved the ecology of their village. 'Batu Into Green' applies to the concept of environmental friendly village. Thus, an analysis was carried out to examine the level of sustainability of this ecology village. This research applied a qualitative approach to descriptively evaluate the current condition of the village based on the principles of the United Nation's Sustainable Development Goals (SDGs). The focus of the SDGs in this discussion is Sustainable Cities and Communities (SDGs No.11). From the analyses, the 'Batu Into Green' initiative has a great potential for economic, social, and cultural sustainability